Hasil Evaluasi Pelaksanaan Dana Alokasi Khusus Pendidikan - APBN RI Tahun 2007 di Provinsi Maluku - Anwar, Khoirul (Bina Nusantara University, 2010)
Improving educational quality and equal learning opportunities in basic education can be achieved if supported by adequate infrastructure. Based on 2006 data on the number of existing facilities and infrastructures indicate that approximately 35% of 131,402 primary schools are still in poor condition and require rehabilitation. To cope with the condition of facilities and infrastructure in primary schools, the Government has implemented various programs, one of which is the Special Allocation Fund Program (DAK) in the Education Sector which has the objective to help fund special activities into regional affairs and is a national priority. This paper aims to provide a snapshot of the flow of funds sourced from the state budget and whether its use is in accordance with the objectives (technical instructions) or there are irregularities. This paper aims also to give a real case in public administration in the era of reform that is absolutely required to keep transparent and accountable records. Samples are taken from schools in the province of Maluku due to their geographic location that are difficult to implement development programs, especially education.